वैदिक यज्ञीय उपकरण: प्रतीकात्मक दृष्टि - Dr. Suman Sharma; Dr. Neetu Saxena (Dr. Chinmay Pandya, 2014)
यज्ञो वै श्रेष्ठतमं कर्म - यज्ञ एक सामान्य कर्म नहीं प्रत्युत सब कर्मों में श्रेष्ठतम कर्म माना गया है। यज्ञ कर्मकाण्ड मात्रा नहीं, प्रत्युत जगत् प्रप/ हेतु प्रजापति द्वारा सम्पादित गूढ़ सृष्टि रहस्य का द्योतक है। यही ब्रह्माण्ड का केन्द्र बिंदु एवं उद्भवस्थल है। निश्चयेन यज्ञ की सभी विधियाँ अथवा कृत्य एवं उनमें प्रयुक्त उपकरण, पात्रादि सभी लौकिक जगत् की वस्तुएँ न होकर प्राकृतिक एवं आध्यात्मिक तत्वों के प्रतीक हैं, जो ब्राह्मण साहित्य में प्रतिपादित यज्ञों में प्रयुक्त उपकरणों की प्रतीकात्मक व्याख्या से स्पष्ट है, उदाहरणार्थ - जल, अनस्, कृष्णाजिन, जुहू, उपभृत, सु्रवा, यूप, उलूखल-मुसल, शूर्प, अग्निहोत्राहवणी, वेदी, बर्ही इत्यादि। यज्ञ की इसी प्रतीकात्मकता के कारण दर्शपौर्णमास को भी तैत्तिरीय संहिता में देवरथ कहा गया है - एष वै देवरथो यद्दर्शपूर्णमासौ। अतः यज्ञ प्रकृति, सृष्टि-प्रक्रिया और आत्मयाग का प्रतीक है। कालांतर में कर्मकाण्ड के प्रभाव के कारण इसका सूक्ष्म रूप तिरोहित हो गया और स्थूलरूप अवशिष्ट रहा। यज्ञ-प्रक्रिया वैदिक दर्शन को समझने, शाश्वत सत्य को प्राप्त करने और परमात्मा को प्राप्त करने का साधन है। वैदिक ऋषियों ने जिस परम सत्य का दर्शन किया उसी को हमने अपने जीवन में उतारना है और उसी के माध्यम से अपने समाज का नव निर्माण करना है। प्रस्तुत शोध-पत्र के माध्यम से यज्ञ के बृहद आयाम को धरण करते हुए केवल प्रतीकात्मक दृष्टि से अध्ययन करने का प्रयास किया है। संसार के सभी धर्मों में यज्ञ किसी न किसी रूप में सदैव प्रचलित रहा है और रहेगा। यज्ञ ही विविध-विधाओं का मूलाधर है। Yajnas are the best deeds - Yagya is not a customary karma rather it is considered to be the supreme karma among all the deeds. Yajna is not a ritualistic step, rather it symbolizes the deep-seated mystery beyond the world. This is the focal point and origin of the universe. All the practices or observance of the Nishchayen Yajna and the instruments used in them, are not the objects of the cosmic world, instead are the symbols of the natural and spiritual elements, which is evident from the symbolic interpretation of the instruments used in the Yajnas propounded in Brahmanical literature, for example - Water, Anasa, Krishnajin, Juhu, Dhrita, Surava, Yupa, Ulukhal-Musal, Shurpa, Agnihotrahavani, Vedi, Barhi etc. Due to this symbolism of the yajna, Darshapournamas has also been called Devrath in the Taittiriya Samhita - Esha Va Devratho Yadarsharpanamasau. Therefore, Yajna is a symbol of nature, creation process and self-sacrifice. In due course of time, due to the effect of ritual, its subtle form disappeared and the gross form remained residual. Yajna-process is a means of understanding Vedic philosophy, attaining eternal truth and God. The Vedic sages have experienced which supreme reality, we have to bring that to our lives and procreate a new civilisation. While endeavouring to study the larger dimensions of the Yajna, only symbolically has been attempted through the present research paper. In all dharmas of the world, yajna has always been and will remain in one or another form . Yagya is the foundation of various doctrines.